The role of CDPKs in plant development, nutrient and stress signaling - Dekomah, Simon Dontoro; Bi, Zhenzhen; Dormatey, Richard; Wang, Yihao; Haider, Fasih Ullah; Sun, Chao; Yao, Panfeng; Bai, Jiangping (Frontiers in Genetics, 2022)
The second messenger calcium (Ca2+) is a ubiquitous intracellular signaling molecule found in eukaryotic cells. In plants, the multigene family of calcium-dependent protein kinases (CDPKs) plays an important regulatory role in plant growth and development and stress tolerance. CDPKs sense intracellular Ca2+ concentration changes and convert them into phosphorylation events that initiate downstream signaling processes. Several functional and expression studies of different CDPKs and their encoding genes confirmed their multi-functional role for stress. Here we review the signaling transduction mechanism and functional roles of CDPKs. This review provided details on; secondary metabolites regulation, nutrient uptake, regulation of flower development, hormonal regulation, and biotic and abiotic stress responses.